International Conference “Ethno-Pedagogy as a Factor of Preservation of the Russian Identity,” Dedicated to the 90th Anniversary of the Birth of Academician of Russian Academy of Education G. N. Volkov - S. L. Mikheyeva; O. A. Dimitriyeva; A. P. Nikitin (Научный диалог)
The overview of the results of the International conference “Ethno-pedagogy as a factor of preservation of the Russian identity,” dedicated to the 90th anniversary of the birth of academician of Russian Academy of Education G. N. Volkov, held 22-24 June in Cheboksary (Chuvash State Pedagogical University named after I. Ya. Yakovlev). It is reported about composition of participants, directions of the conference, thematic areas, student competition.